Decreased Expression of Hepatocyte Nuclear Factor 4α (Hnf4α)/MicroRNA-122 (miR-122) Axis in Hepatitis B Virus-associated Hepatocellular Carcinoma Enhances Potential Oncogenic GALNT10 Protein Activity - Wu, Qian (J Biol Chem, 2015)
MicroRNA-122 (miR-122), a mammalian liver-specific miRNA, has been reported to play crucial roles in the control of diverse aspects of hepatic function and dysfunction, including viral infection and hepatocarcinogenesis. In this study, we explored the clinical significance, transcriptional regulation, and direct target of miR-122 in hepatitis B virus (HBV)-associated hepatocellular carcinoma. Reduced expression of miR-122 in patients with HBV-associated hepatocellular carcinoma was correlated with venous invasion and poor prognosis. Furthermore, UDP-N-acetyl-α-d-galactosamine:polypeptide N-acetylgalactosaminyltransferase-10 (GALNT10) was identified as a bona fide target of miR-122 in hepatoma cells. Ectopic expression and knockdown studies showed that GALNT10 indeed promotes proliferation and apoptosis resistance of hepatoma cells in a glycosyltransferase-dependent manner. Critically, adverse correlation between miR-122 and GALNT10, a poor prognosticator of clinical outcome, was demonstrated in hepatoma patients. Hepatocyte nuclear factor 4α (Hnf4α), a liver-enriched transcription factor that activates miR-122 gene transcription, was suppressed in HBV-infected hepatoma cells. Chromatin immunoprecipitation assay showed significantly reduced association of Hnf4α with the miR-122 promoter in HBV-infected hepatoma cells. Moreover, GALNT10 was found to intensify O-glycosylation following signal activation of the epidermal growth factor receptor. In addition, in a therapeutic perspective, we proved that GALNT10 silencing increases sensitivity to sorafenib and doxorubicin challenge. In summary, our results reveal a novel Hnf4α/miR-122/GALNT10 regulatory pathway that facilitates EGF miR-122 activation and hepatoma growth in HBV-associated hepatocarcinogenesis.